TRADISI PERAWATAN IBU HAMIL DALAM MASYARAKAT DI KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR - Rada Junitia; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Kemuning Sub-district of Indragiri Hilir Regency with title of research of Tradition of Pregnant Mother Care in Society. This study aims to determine the stages of women's care in the community of Kemuning Sub-district Indragiri Hilir and to know if the tradition value in pregnant women treatment already conform with the medic treatment in the clinic. This research is descriptive qualitative research. Subjects in this study consist of 9 people, midwives and customs leaders who can help researchers. The purpose of purposive sampling is to adjust to research objectives. The data collection of reports using guidelines. The results show that currently rituals are still performed pregnant women in the Malay community. Pregnancy care pregnant women are not free from the help of a shaman and many taboos that should not be done by a pregnant woman. The food that do not allowed to consume by the pregnant women consist of some animal and begetable. Pregnant women apply some things that should not be done during pregnancy. The role of a husband in pregnancy is to lead the wife to studying pregnancy, while the role of in-laws or parents during pregnancy is to help with homework such as cooking and other homework. In the family of pregnancy care is the routine exams and the implementation of midwife messages, continue pregnancy abstinence, consultation to the midwife when it is sick, regards the message of the family, often eat cashew for the confidence of the child's skin Is born white later (it is Believed By the Malay community) and to the dentist there are sick. Family and midwife are sources of information. Safe information in pregnancy care is information that comes from a midwife.Keywords; Tradition, pregnant women’s care, Malay ssociety